Upaya Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa SMP Ahmad Dahlan Kota Jambi - Efni, Nel; Fatmawati, Tina Yuli (Universitas Baiturrahim, 2024)
The health problems of school children today are increasingly complex. For school children, this is usually related to Clean and Healthy Living Behavior (PHBS) such as washing hands properly, consuming healthy snacks, exercising regularly and so on. This healthy behavior should be started as early as possible, because child care habits, including health care provided by parents, will directly influence the child's subsequent healthy behavior. The aim of this community service is to increase students' knowledge about clean and healthy living behavior. The service methods applied are lectures, discussions, mentoring. Service activities for 35 students took place at Ahmad Dahlan Middle School, Jambi City. The results of the activity showed that 28 students (80%) had less knowledge about PHBS pretest. After being given education, the knowledge results increased to 31 people (91.25%), it can be concluded that there was an increase in students' knowledge after being given health education about PHBS. It is hoped that schools will further increase promotive and preventive activities regarding the importance of clean and healthy living behavior.